Osteologia craniana de Platalea ajaja (Linnaeus) (Aves, Ciconiiformes), comparada com outras espécies de Threskiornithidae - Ferreira, Carolina D. [UNESP]; Donatelli, Reginaldo José [UNESP] (Sociedade Brasileira de Zoologia, 2005)
Platalea ajaja (Linnaeus, 1758) pertence Threskiornithidae (curicacas e afins e colhereiros), Threskiornithoidea, Ciconiiformes. Threskiornithidae (colhereiros, curicacas e afins) são subdivididos em dois grupos: Threskiornithinae que compreende curicacas e afins, caracteriza-se por seus representantes possuírem um bico longo, estreito e curvo, ao passo que Plataleinae inclui os colhereiros, que apresentam bico longo e achatado na ponta. O presente trabalho teve como objetivo descrever a osteologia craniana de P. ajaja (Plataleinae) e comparar com outras espécies pertencentes à Threskiornithinae. As espécies utilizadas para tal comparação foram: Mesembrinibis cayennensis (Gmelin, 1789), Phimosus infuscatus (Lichteinstein, 1823), Theristicus caudatus (Boddaert, 1783) e Plegadis chivi (Vieillot, 1817). Outras espécies pertencentes a ordem Ciconiiformes também foram utilizadas para comparação. A partir do presente estudo, observou-se que P. ajaja (Plataleinae) apresenta como características que a separa dos Threskiornithinae: 1) sutura frontonasal conspícua; 2) processo supra-orbital do osso lacrimal curto; 3) maxila superior achatada dorsoventralmente, sendo alargada na extremidade, tomando forma de uma colher; 4) narina curta e de forma oval; e 5) processo retroarticular curto. Entretanto, são necessários estudos osteológicos que contemplem as outras espécies da família, bem como um estudo filogenético do grupo para maior compreensão das relações existentes entre os Threskiornithidae.

Platalea ajaja (Linnaeus, 1758) belongs to the Threskiornithidae (ibises and spoonbills), Threskiornitoidea, Ciconiiformes. The Threkiornithidae are currently divided into two groups: Threskiornithinae (ibises and allies), which have curved bills used to probe into the mud, and Plataleinae that have specialized flat bill shapes. The goal of the present work was to describe the cranial osteology of P. ajaja (Plataleinae) and compare it with other species of the family Threskiornithidae. Other species pertaining to the order Ciconiiformes were also considered for analyses and comparison with the former one. The results showed that P. ajaja presents many distinct characteristics from others species of the same family as: the shape of the upper jaw, dorsoventrally flattend, larger on the maxillar surface, taking a characteristic shape of a spoon; a conspicuous frontonasal suture; a short supraorbital process of the lacrimal bone; a conspicuous and sharp lateral process of the paraesphenoid bone; the nares are short with an oval shape; a short retroarticular process of the mandible; a short projection of the parasphenoid bone; a dorsoventrally flattened mandible. The characteristics shared between P. ajaja and other Threskiornithidae are: frontal and lacrimal bones not fused; well developed lacrimal bone, zigomatic and paroccipital processes; occipital fonticuli present; nares located in a ridge of the premaxillar bone; reduced maxillar bone; a conspicuous and laterally flattened vomer. However, it is necessary more osteological studies with other species of the same family and a phylogenetic analysis of the group for better understanding of the relationships among the Threskiornithidae.
Skull osteology of Platalea ajaja (Linnaeus) (Aves, Ciconiiformes), compared with others species of Threskiornithidae
Keywords: Anatomia; aves; colhereiros; crânio; curicacas; Anatomy; birds; Ibis; Roseate Spoonbill; skull